Glossary of aquaculture = (Food and Agriculture Organization of the United Nations, 2008)
The glossary was prepared by the Aquaculture Management and Conservation Service of the United Nations Food and Agriculture Organization. By providing standard definitions and translations of terms, it is designed to facilitate communication between technical experts and scientists involved in aquaculture research and development. A second goal is to enhance communication between aquaculture research and development technicians and scientists; developers; consultants; and users from other disciplines such as administrators, agriculturists, economists, engineers, environmentalists, and policy makers. It is available in each of the five official languages of the Food and Agriculture Organization, and each version provides translations and indexes of terms in the other four languages. Updates are expected as users respond to the first edition. Annotation ©2009 Book News, Inc., Portland, OR (booknews.com)